Key writers on art from antiquity to the nineteenth century - Murray, Chris (Routledge Key Guides., 2003)
Key Writers on Art: From Antiquity to the Nineteenth Century offers a unique and authoritative guide to theories of art from Ancient Greece to the end of the Victorian era, written by an international panel of expert contributors. Arranged chronologically to provide an historical framework, the 43 entries analyze the ideas of key philosophers, historians, art historians, art critics, artists and social scientists, including Plato, Aquinas, Alberti, Michelangelo, de Piles, Burke, Schiller, Winckelmann, Kant, Hegel, Burckhardt, Marx, Tolstoy, Taine, Baudelaire, Nietzsche, Ruskin, Pater, Wölfflin and Riegl.Each entry includes:• a critical essay• a short biography• a bibliography listing both primary and secondary textsUnique in its range and accessibly written, this book, together with its companion volume Key Writers on Art: The Twentieth Century, provides an invaluable guide for students as well as general readers with an interest in art history, aesthetics and visual culture.